Radiation therapy in functioning and no functioning pituitary neuroendocrine tumor: systematic review of the recent literature after 2011 - Hemaidia, Racha-Miloda; Cebula, Hélène; Goichot, Bernard; Noel, Georges (Frontiers in Endocrinology, 2024)
Neuroendocrine pituitary tumor, a benign cells proliferation, can cause significant morbidity due to its local invasiveness and secretory properties. Historically, radiotherapy has been employed as a second or third-line treatment option, with studies dating back to the mid-20th century. However, advancements in radiotherapy techniques, such as intensity-modulated radiation therapy (IMRT), stereotactic radiosurgery, and proton therapy, have revolutionized treatment approaches. This review aims to critically evaluate the recent literature (2011-2022) on the use of radiotherapy in both functioning and nonfunctioning neuroendocrine pituitary tumor. We employed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology to systematically analyze 52 articles, focusing on local and hormonal control, radiotherapy protocols, and treatment-related side effects.